A Narrative Review of Teaching Vocabulary Through Videos: Insights and Strategies for Young Learners - Kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2024)
Vocabulary plays a critical role in language acquisition, serving as the foundation for developing speaking, listening, reading, and writing skills. However, young learners often face challenges in acquiring vocabulary due to the need for engaging and context-rich learning tools. This study aims to investigate the effectiveness of videos in teaching vocabulary to young learners by analyzing findings from recent studies. Using a narrative literature review, three articles published between 2020 and 2023 were examined to identify the types of videos used, teaching strategies employed, and their impact on learners. The findings reveal that videos, including animated and YouTube-based content, significantly enhance vocabulary acquisition by promoting active engagement, improving comprehension, and increasing motivation. Effective teaching strategies such as freeze framing, replication, and active viewing were identified as key to maximizing learning outcomes. This study highlights the importance of thoughtful integration of video content to meet young learners' needs and improve vocabulary learning.